Study of Medical and Biological Properties of Zinc Lysinate-Riboflavinate - Qasim Shakir Kadhim (Journal of Global Pharma Technology, 2019)
Biomedical houses about the Zinc-lysinitroboflavinate a new colloidal chelate structure over zinc address microelement are investigated within the case on the work. Intragastric ruler of a hundred mg/kg regarding zinc lysinate-riboflavinate in imitation of experimental animals does no longer cause signs regarding toxicological effects. Toxicological tests on zinc lysinate-riboflavinate have been conducted outdoors over the basis concerning the department about remedy and pharmacology regarding the Faculty regarding Veterinary Medicine on StSAU. The give phase arrangement about zinc lysinate-riboflavinate aqueous solutions was once investigated with the aid of the method over photon-correlation spectroscopy within the laboratories about the branch on technological know-how over Nanomaterials (NCFU, Engineering Institute).Keyword: Zinc-lysinitroboflavinate, biomedical properties, toxicological effects.